The Effect of Pin Shape on the Friction Stir Welding Quality of Aluminum AA1100 Series - Irza Sukmana (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2022)
Aluminum is a material that is soft, lightweight, resistant to corrosion, and has good electrical and thermal conductivity. Aluminum has a specific gravity of about 2.65-2.8 kg/dm³, a melting point of 658ºC, and tensile strength of 90 MPa. Aluminum 1100 series is an aluminum alloy mixed with other materials, such as copper, iron, chrome, manganese, and zinc, with an aluminum content of 99,0%. Welding is the joining of two metals in a liquid state with or without filler. FSW (friction stir welding) is friction welding; the process does not require filler material. The heat used to melt the metal is obtained from the friction between the indenter and the workpiece. In the research, the shape of the indenter pin used is, ovale shape, cone shape, and changing spiral form with a tool rotation of 2000 rpm and a welding rate of 16 mm/minute. The tests carried out are Rockwell hardness testing and tensile tests. From the results of research conducted, it was found that the shape of the indenter pin greatly affects the quality of the weld. The indenter pin changing spiral form results in better weld quality compared to the other two pin shapes.